Socialization and Assistance Program for Plastic Waste Recycling using Ecobrick Method at SDN Kawungsari, Bandung Regency, Indonesia - Herliana, Erika; Cahyana, Sukma; Setiaji, Hessa (Abdimas Indonesian Journal, 2025)
Plastic waste is a significant environmental issue, particularly due to its slow decomposition and incresing accumulation. One solution to mitigate plastic waste is the Ecobrick method., where non-organic plastic is compacted into plastic bottles to create durable building materials. This study focuses on the socialization and assistance program for plastic waste recycling using Ecobrick method at SDN Kawungsari, Bandung Regency. The program aims to raise awareness among students and the community about the importance of waste separation and the potential of Ecobricks, along with follow-up assistance to ensure continuous practice. Surveys and observations were conducted before and after the program to measure changes in knowledge, attitudes, and participation levels regarding plastic waste recycling. The result showed a significant increase in awareness and active involvement from students and teachers in the creation of Ecobrick. This initiative demonstrates the potential of educational interventions to foster sustainable waste management practices in local communities.